2017
DOI: 10.1038/s41598-017-16621-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication by orang-utans (Pongo pygmaeus) using bioactive properties of Dracaena cantleyi

Abstract: Animals self-medicate using a variety of plant and arthropod secondary metabolites by either ingesting them or anointing them to their fur or skin apparently to repel ectoparasites and treat skin diseases. In this respect, much attention has been focused on primates. Direct evidence for self-medication among the great apes has been limited to Africa. Here we document self-medication in the only Asian great ape, orang-utans (Pongo pygmaeus), and for the first time, to our knowledge, the external application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Triplicates from at least three independent experiments were used. For the ELAM assay, the Calcein AM (Molecular Probes, Invitrogen, Karlsruhe, Germany) cytotoxicity assay, which assessed HUVEC viability after 4 h treatment, was used as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Triplicates from at least three independent experiments were used. For the ELAM assay, the Calcein AM (Molecular Probes, Invitrogen, Karlsruhe, Germany) cytotoxicity assay, which assessed HUVEC viability after 4 h treatment, was used as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay (ELISA) was used to detect the levels of the cell adhesion molecule ELAM in HUVEC cells after 30 min of incubation with the tested compounds and 4 h of stimulation with TNFα, as previously described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly relevant for human evolution since humans and non-human primates share a common evolutionary history and have a similar physiology and it is possible that they share ways to combat diseases through medicinal plant use (Huffman 2016 ). This includes studies of chimpanzees ( Pan troglodytes ) and gorillas ( Gorilla gorilla ) (Basabose 2002 ; Cousins and Huffman 2002 ; Rogers et al 2004 ; Huffman 2001 , 2003 , 2015 ; Huffman and Seifu 1989 ; Huffman et al 1996 ; Mclennan and Huffman 2012 ; Krief et al 2006 ; Masi et al 2012 ), Japanese macaques ( Macaca fuscata ) (Huffman et al 2010 ; Tasdemir et al 2020 ), sifakas ( Propithecus verreauxi verreauxi ) (Carrai et al 2003 ), lemurs ( Eulemur rufifrons ) (Peckre et al 2018 ), Tibetan macaques ( Macaca thibetana ) (Huffman et al 2020 ), and orangutans ( Pongo pygmaeus ) (Morrogh-Bernard et al 2017 ). Some of these studies have demonstrated both health maintenance and deliberate self-medication that is processed using a combination of innate mechanisms, individual learning, and cultural transmission (Huffman 2016 ).…”
Section: Evolutionary Contextmentioning
confidence: 99%
“…A recent example of the reverse, human-animal adaptation, has also been observed in the emerging use of soap by ring-tailed coati ( Nasua nasua ) that live near a tourist complex on Ilha do Campeche, Brazil (Gasco et al 2016 ). A good example of human-animal correlation can be found in orangutans collecting leaves of Dracaena cantleyi Baker, Asparagaceae, that they mix with saliva and rub onto parts of the body, something that is also done by the local indigenous population, who rub a poultice of this plant on parts of the body to relieve pain (Morrogh-Bernard et al 2017 ).…”
Section: Evolutionary Contextmentioning
confidence: 99%
“…The use of medicinal plants by non-human primates may also involve different plant parts. For instance, some orangutans ( Pongo pygmaeus ) in Indonesia ingest Dracaena cantleyi leaves for the treatment of parasites [ 40 ]. Although the therapeutic use of plants is understood to be essential for the survival and evolution of hominids, the events that led to this behavior are still uncertain, with only few hypotheses about its origin (for a complete argument see Albuquerque et al [ 33 ]).…”
Section: Introductionmentioning
confidence: 99%